Mechanical stimulation induces rapid fibroblast proliferation and accelerates the early maturation of human skin substitutes. (June 2021) - Wahlsten, Adam; Rütsche, Dominic; Nanni, Monica; Giampietro, Costanza; Biedermann, Thomas; Reichmann, Ernst; Mazza, Edoardo
Abstract: The clinical treatment of large, full-thickness skin injuries with tissue-engineered autologous dermo–epidermal skin substitutes is an emerging alternative to split-thickness skin grafting. However, their production requires about one month of in vitro cell and tissue culture, which is a significant drawback for the treatment of patients with severe skin defects. With the aim to reduce the production time, we developed a new dynamic bioreactor setup that applies cyclic biaxial tension to collagen hydrogels for skin tissue engineering. By reliably controlling the time history of mechanical loading, the dynamic culturing results in a three-fold increase in collagen hydrogel stiffness and stimulates the embedded fibroblasts to enter the cell cycle. As a result, the number of fibroblasts is increased by 75% compared to under corresponding static culturing. Enhanced fibroblast proliferation promotes expression of dermal extracellular matrix proteins, keratinocyte proliferation, and the early establishment of the epidermis. The time required for early tissue maturation can therefore be reduced by one week. Analysis of the separate effects of cyclic loading, matrix stiffening, and interstitial fluid flow indicates that cyclic deformation is the dominant biophysical factor determining fibroblast proliferation, while tissue stiffening plays a lesser role. Local differences in the direction of deformation (in-plane equibiaxial vs. uniaxial strain) influence fibroblast orientation but not proliferation, nor the resulting tissue properties. Importantly, dynamic culturing does not activate fibroblast differentiation into myofibroblasts. The present work demonstrates that control of mechanobiological cues can be very effective in driving cell response toward a shorter production time for human skin substitutes.